IMPROVEMENT OF VITAMIN-D DEFICIENT RACHITISTREATMENT IN CHILDREN (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Introduction:Significant changes of the highest fatty acids content were revealed in the blood serum in children ill withrachitis. The depth of changes of the highest fatty acids content depended on the degree of the pathologic process severity.The revealed disturbances of the highest fatty acids content was corrected by means of apricot oil and the results of therapywere presented. Efficacy of the presented method of treatment in children with rachitis was shown in optimal doses ofapricot oil.Methods: 67 patients ill with Vitamin-D deficient rachitis and 10 practically healthy children of the control group wereenrolled in the study. The 1stdegree of the disease was diagnosed in 30 (44,8%) and the 2nddegree in 37 (55,2%)children.The content of the highest fatty acids in blood serum of the studied patients was determined by means of gas- liquidchromatography. For identification of separated methyl aether fatty acids the method of “witness” and “sorbentsorbat”method based on structural group contents were used.Results:67 babies were studied. In children with Vitamin-D deficient rachitis the content of such fatty acids as palmitinic,strearic and linolic acids increases and palmitoleinic, oleic, linoleic and arachidonic acids decreases and that is the evidenceof lipid exchange disturbance in rachitis. It motivates the necessity to correct lipid exchange in this pathology and to addvegetable oils. In order to eliminate dysmetabolism of the highest fatty acids in children with rachitis it is recommended toadminister apricot oil as therapeutic agent.Conclusion:In order to eliminate the highest fatty acids dysmetabolism in children ill with rachitis it is recommended toadminister apricot oil that results in restoration of the highest fatty acids metabolism and provides high therapeutic effect.